Economic analysis of prenatal fetoscopic vs open‐hysterotomy repair of open neural tube defect. (13th July 2021) - King, B. C.; Hagan, J.; Corroenne, R.; Shamshirsaz, A. A.; Espinoza, J.; Nassr, A. A.; Whitehead, W.; Belfort, M. A.; Sanz Cortes, M.
ABSTRACT: Objective: Fetal repair of an open neural tube defect (ONTD) by open hysterotomy has been shown to reduce the need for ventriculoperitoneal shunting and improve motor outcomes for infants, but increases the risk of Cesarean section and prematurity. Fetoscopic repair is an alternative approach that may confer similar neurological benefits but allows for vaginal delivery and reduces the incidence of hysterotomy‐related complications. We sought to compare the costs of care from fetal surgery until neonatal discharge, as well as the clinical outcomes, associated with each surgical approach. Methods: This was a retrospective cohort study of patients who underwent prenatal ONTD repair, using either the open‐hysterotomy or the fetoscopic approach, at a single institution between 2012 and 2018. Clinical outcomes were collected by chart review. A cost–consequence analysis was conducted from the hospital perspective, and included all inpatient and ambulatory hospital and physician costs incurred for the care of mothers and their infants, from the time of maternal admission for fetal ONTD repair up to postnatal maternal and infant discharge. Costs were estimated using cost‐to‐charge ratios for hospital billing and the Medicare physician fee schedule for physician billing. Results: Seventy‐eight patients were included in the analysis, of whom 47 underwent fetoscopic repair and 31 underwent open‐hysterotomy repair. In the fetoscopic‐repair group, compared with the open‐repair group, fewer women underwent Cesarean section (53% vs 100%; P  < 0.001) and the median gestational age at birth was significantly higher (38.1 weeks (interquartile range (IQR), 35.2–39.1 weeks) vs 35.7 weeks (IQR, 33.9–37.0 weeks); P  < 0.001). No case of uterine dehiscence was observed in the fetoscopic‐repair group, compared with an incidence of 16% in the open‐repair group. After adjusting for baseline characteristics, there was no significant difference in the total cost of care between the fetoscopic‐repair and the open‐repair groups (median, $76 978 (IQR, $60 312–$115 386) vs $65 103 (IQR, $57 758–$108 103); P  = 0.458). Conclusions: Fetoscopic repair of ONTD, when compared with the open‐hysterotomy approach, reduces the incidence of Cesarean section and preterm delivery with no significant difference in total costs of care from surgery to infant discharge. This novel approach may represent a cost‐effective alternative to improve maternal and neonatal outcomes for this high‐risk population. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.